2013
DOI: 10.1111/mec.12282
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype structure, adaptive history and associations with exploratory behaviour of theDRD4gene region in four great tit (Parus major) populations

Abstract: The assessment of genetic architecture and selection history in genes for behavioural traits is fundamental to our understanding of how these traits evolve. The dopamine receptor D4 (DRD4) gene is a prime candidate for explaining genetic variation in novelty seeking behaviour, a commonly assayed personality trait in animals. Previously, we showed that a single nucleotide polymorphism in exon 3 of this gene is associated with exploratory behaviour in at least one of four Western European great tit (Parus major)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 75 publications
(187 reference statements)
1
49
1
Order By: Relevance
“…Subsequent sequencing of the PCR products revealed 9 SNPs, 7 located in the promoter region (detailed in Table 1). 11,12 the In/del ID15 was not observed in our populations. Two SNPs were observed in exon 1 of the DRD4 gene.…”
Section: Extensive Genotyping Of the Drd4 Promoter Interval In Great Titcontrasting
confidence: 67%
See 2 more Smart Citations
“…Subsequent sequencing of the PCR products revealed 9 SNPs, 7 located in the promoter region (detailed in Table 1). 11,12 the In/del ID15 was not observed in our populations. Two SNPs were observed in exon 1 of the DRD4 gene.…”
Section: Extensive Genotyping Of the Drd4 Promoter Interval In Great Titcontrasting
confidence: 67%
“…However, although earlier works found an association between DRD4 SNP830 polymorphism and novelty seeking in great tits, 10 this association was only found in one population. 11,12,43 More recently, the SERT gene has been suggested as one of the candidate genes for local adaptation to novel conditions and urbanization. 13 Since we found that one of the main differences between urban and forest great tits probably relied on personality, 27,44 we thought that it could be valuable to look for a direct relationship between SERT polymorphisms, in addition to DRD4, and personality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…association study to detect a significant association with personality traits for several great tit populations (Mueller et al 2013). Although the link between DNA methylation and gene expression is not always straightforward (Jones 2012), we hypothesize that differential methylation at the DRD4 gene affects gene activity and ultimately personality variation.…”
Section: Discussionmentioning
confidence: 82%
“…In great tits (Parus major), allelic variants in exon 3 of the DRD4 gene are statistically associated with exploratory behaviour in experimental populations that were selected for divergent levels of exploratory behaviour and in hand-reared wild birds (Fidler et al 2007) and also in some (but not all) natural populations (Korsten et al 2010;Mueller et al 2013). However, the observed association could not be linked to any functional (nonsynonymous) single nucleotide polymorphism (SNP) or deletion site within the DRD4 gene or its flanking regions, although there were signs of selection for this polymorphism (Korsten et al 2010;Mueller et al 2013). Thus, DRD4 seems to play a role in heritable variation in great tit exploratory behaviour, but the underlying molecular mechanism remains to be demonstrated.…”
Section: Introductionmentioning
confidence: 99%